Phylogenetics, integrative taxonomy and systematics of the Sesamia cretica species group (Lepidoptera: Noctuidae: Apameini: Sesamiina), with the description of 21 new species from the Afrotropical region - (:unkn) unknown (My University, 2022)
In this study, 31 species of noctuid stemborers belonging to the genus Sesamia Guenee, 1852 (Lepidoptera: Noctuidae: Noctuinae: Apameini: Sesamiina) are reviewed. All these species are assigned to the Sesamia cretica group sensu Tams & Bowden (1953). Based on genitalic characters, several subgroups are hereby defined. Nine species belong to a species complex defined as the Sesamia albivena Hampson, 1902 subgroup; it consists of S. albivena, S. mocoensis Tams & Bowden, 1953, n. stat., S. sudanensis Tams & Bowden, 1953, n. stat. S. taenioleuca (Wallengren, 1863), and five new species that are described (S. aethiopica Le Ru n. sp. from Ethiopia, S. kafulo Le Ru n. sp. from Botswana and Zambia, S. kavirondo Le Ru n. sp. from Kenya and Uganda, S. maloukou Le Ru n. sp. from Republic of Congo, and S. soyema Le Ru n. sp. from Ethiopia). Four species belong to a species complex defined as the Sesamia cretica subgroup; this encompasses S. cretica, S. rufescens Hampson, 1910, and two new species that are described (S. ihambane Le Ru n. sp. from Mozambique and Tanzania and S. kikuyuensis Le Ru n. sp. from Kenya); two new synonyms are introduced for Sesamia cretica: Nonagria uniformis Dudgeon, 1905 n. syn. and Sesamia griselda Warren, 1913, n. syn. Ten species belong to a species complex defined as the Sesamia fuscifrontia Hampson, 1914 subgroup; this includes S. fuscifrontia, S. geyri (Strand, 1915) and eight new species that are described (S. babati Le Ru n. sp. from Tanzania, S. babessi Le Ru n. sp. from Cameroon and Zambia, S. mabira Le Ru n. sp. from Uganda, S. nangaensis Le Ru n. sp. from Cameroon and Republic of Congo, S. rungwa Le Ru n. sp. from Tanzania, S. simillima Le Ru n. sp. from Benin, Cameroon, Kenya and Uganda, S. taveta Le Ru n. sp. from Kenya and S. ulaukae Le Ru n. sp. from Ethiopia). One species belongs to a species complex defined as the Sesamia salama Le Ru n. sp. subgroup; this consists of S. salama Le Ru n. sp. from
Keywords: African Research